Robinson Crusoe in Asia
XIII, 306 p. 5 illus., 2 illus. in color.
Keywords: This collection of essays expands the study of that immensely widely read and much-adapted novel, beyond the first book – The Life and Strange Surprising Adventures of Robinson Crusoe (usually known simply as Robinson Crusoe) – to take in the far less well-known Farther Adventures and the almost unread Serious Reflections, beyond Defoe’s texts, to their re-writing and adaptation and beyond the Atlantic and South American context to an Asian and Pacific context. The essays consider both how Asia is represented in the books (in terms of politics, economics, religion), and how the book has been received, adapted, and taught, particularly in Asian contexts.